Lung function measurements in rodents in safety pharmacology studies - Hoymann, Heinz G. (Frontiers in Pharmacology, 2012)
The ICH guideline S7A requires safety pharmacology tests including measurements of pulmonary function. In the first step – as part of the “core battery” - lung function tests in conscious animals are requested. If potential adverse effects raise concern for human safety, these should be explored in a second step as a “follow-up study”. For these two stages of safety pharmacology testing, both noninvasive and invasive techniques are needed which should be as precise and reliable as possible. A short overview of typical in-vivo measurement techniques is given, their advantages and disadvantages are discussed and out of these the noninvasive head-out body plethysmography and the invasive but repeatable body-plethysmography in orotracheally intubated rodents are presented in detail. For validation purposes the changes in the respective parameters such as tidal midexpiratory flow (EF50) or lung resistance have been recorded in the same animals in typical bronchoconstriction models and compared. In addition, the technique of head-out body plethysmography has been shown to be useful to measure lung function in juvenile rats starting from day two of age. This allows safety pharmacology testing and toxicological studies in juvenile animals as a model for the young developing organism as requested by the regulatory authorities (e.g. EMEA Guideline 1/2008). It is concluded that both invasive and noninvasive pulmonary function tests are capable of detecting effects and alterations on the respiratory system with different selectivity and area of operation. The use of both techniques in a large number of studies in mice and rats in the last years have demonstrated that they provide useful and reliable information on pulmonary mechanics in safety pharmacology and toxicology testing, in investigations of respiratory disorders, and in pharmacological efficacy studies.